2006
DOI: 10.1007/s10729-006-7661-z
|View full text |Cite
|
Sign up to set email alerts
|

A new organ transplantation location–allocation policy: a case study of Italy

Abstract: In this paper, we propose a location model for the optimal organization of transplant system. Instead of simulation approach, which is typical when facing many health care applications, our approach is distinctively based on a mathematical programming formulation of the relevant problem. In particular, we focus on the critical role of time in transplantation process as well as on a spatial distribution of transplant centers. The allocation of transplantable organs across regions with the objective of attaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 22 publications
0
40
0
Order By: Relevance
“…Most work related to organ donations and organ transplants focuses on policies to allocate organs to recipients (see [6,24], and references therein). Within this domain, kidney and liver transplants are most frequently studied, since they constitute the vast majority of transplanted organs (Belgium is no exception, as can be observed from Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Most work related to organ donations and organ transplants focuses on policies to allocate organs to recipients (see [6,24], and references therein). Within this domain, kidney and liver transplants are most frequently studied, since they constitute the vast majority of transplanted organs (Belgium is no exception, as can be observed from Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bruni et al [6] and Kong et al [18] are, as far as we know, the only papers in location theory related to organ transplants. Bruni et al [6] present a mixed integer linear programming (MILP) model that selects the optimal location of recipient centers, donor centers and organ procurement organizations (OPOs).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Depending on the situation, a characteristic of the system may be more or less important to model (e.g., modeling a dynamic system with active individuals may be particularly interesting when studying the impact of a policy on health behavior, because this impact depends on individuals' adaptation and may vary over time). Some studies reported in their limitations that their model lacked dynamic [56,62], stochastic [57,75] or individual heterogeneity [25]. These concerns reflect the different considerations that must be balanced when developing any simulation model: the accuracy of the model, its validity and its applicability.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all reported models included more than one level of factors, e.g., cold-ischemia time of an organ transplant (endogenous), waiting time of the patient (individual), location of the health center (neighborhood) and allocation rules (policy) [57].…”
Section: Characteristics Of the System Modeledmentioning
confidence: 99%
“…A solution that compromises these conflicting objectives may help a central decision maker in developing effective and sustainable public health-care systems. In this context, Bruni et al (2006) propose a binary integer programming model to locate transplant centres by using an objective function incorporating both total travel distance and maximum waiting list size, which is the equity criterion forced to decrease by the model. Furthermore, Gu et al (2010) analyse a bi-objective model with the objectives of maximizing coverage and maximizing participation.…”
Section: Literature Reviewmentioning
confidence: 99%